Assessment of Nurses – Midwives Practices Regarding Prolonged Labor in Babylon Governorate - Homadi, saadia; ali, Rabia (Iraqi National Journal of Nursing Specialties, 2005)
Objective : to assess the nurse-midwives practices regarding prolonging labor in Babylon Governorate hospitals . Methodology : Purposive sample of (57) nurse-midwives, which was selected from (6) hospitals included (3) General Hospital, (2) Maternity Hospital and Teaching Hospital .These nurse-midwives represented several nursing educational levels. A questionnaire was constructed for the purpose of the study, which was comprised demographic characteristics, information a bout nurse-midwives related to their ages, marital status, educational level, experience years in nursing and delivery , and attending midwifery courses through out their work . Results :The study findings indicated that , there were a significant relation ship between the nurse-midwives practices regarding prolonged labor and their ages (x2 = 23.434. P <0.05 ) , Marital status (x2=12.088 . P < 0.05) , and the experience years in delivery room (x2=17.8. P < 0.05) , while there was no significant relation between the nurse-midwives practices and their educational level (x2 =11.153. P < 0.05) . The study concluded that these results regarding the nurse-midwives practices certainly unsatisfactory and effects the type of care given to laboring women with low progress labor . Recommendation: The study recommended that an educational program can be designed and constructed for nurse-midwives through the program , an emphasis can be directed and oriented toward the laboring process. The nurse-midwives can be encouraged for being participated in a special training programs designed and constructed to fulfill the nurse-midwives needs concerning defects and limitations in their practices. collaborative work can be issued between ministry of health and higher education to provide such program. Key Wards: Assessment, Midwives practices, Prolonged labor.